HUMANISME SEBAGAI DASAR PEMBENTUKAN ETIKA RELIGIUS; DALAM PERSPEKTIF IBNU ATHĀ’ILLAH AL-SAKANDARĪ - Fermadi, Bayu (JURNAL ISLAM NUSANTARA, 2018)
At the level of reality, ethics is a social action that can affect all human social action, whether he is good or bad. Universal, the realization of the roles and actions referred to, can not be separated from the internalization of social values that influence it and one of them is about ethics. Therefore, this study wants to build ethics through Ibnu AthÄ'illah's thought concept with his religious humanism as a process towards the formation of the ethics. In the view of Ibn AthÄ'illah social ethics can be built through several processes, namely religious, theological, morality, scriptural, philosophical ethics. The striking difference that religious ethics holds is primarily rooted in the Qur'an and as-Hadith, which significantly tends to release the dialectics and focuses on efforts to expel the spirit of Islamic morality in a more specific way to the study of religious ethics of Ibnu AthÄ 'illah that tries to get out of the craze of developing thoughts and passively chooses social problems. So came the concept of religious ethics that are universal like sincere, patient, honest and trustworthy.